2015
DOI: 10.1371/journal.pone.0120959
|View full text |Cite
|
Sign up to set email alerts
|

Expectant Parents’ Understanding of the Implications and Management of Fever in the Neonate

Abstract: ObjectiveWe estimated the extent to which Canadian expectant parents would seek medical care in a febrile neonate (age 30 days or less). We also evaluated expectant parents’ knowledge of signs and symptoms of fever in a neonate, and explored the actions Canadian expectant parents would take to optimize the health of their child.MethodsWe conducted a cross-sectional survey of a sample of expectant parents from a large urban center in Canada. We recruited participants from waiting rooms in an obstetrical ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…These efforts will need to consider the persistent gap in knowledge and behaviour about the early detection of at-risk situations. For example, a Canadian study found that nearly one-fifth of expectant parents (17%) reported that they would not seek medical care for their febrile neonate (11) and a French population-based study reported a delay in seeking medical care in one-third of fatal cases of febrile bacterial infections (12). The key to reassuring parents and professionals alike is to provide good safety net advice for parents and professionals, covering when parents should seek help from a professional and when healthcare professionals should refer a child for investigation or specialist care (7).…”
mentioning
confidence: 99%
“…These efforts will need to consider the persistent gap in knowledge and behaviour about the early detection of at-risk situations. For example, a Canadian study found that nearly one-fifth of expectant parents (17%) reported that they would not seek medical care for their febrile neonate (11) and a French population-based study reported a delay in seeking medical care in one-third of fatal cases of febrile bacterial infections (12). The key to reassuring parents and professionals alike is to provide good safety net advice for parents and professionals, covering when parents should seek help from a professional and when healthcare professionals should refer a child for investigation or specialist care (7).…”
mentioning
confidence: 99%